Effects of vitamins C and E on erythrocytes and blood chemistry profile of shika brown layer hens transported by road. - Ajakaiye, J.J.; Ayo, J.O.; Musa, D. (Instituto de Ecología, A.C., 2010)
This study was conducted to determine the effects of dietary supplementation of vitamin C (l- ascorbic acid) and vitamin E (dl-·-tocopherol acetate) on some erythrocytes and blood chemistry parameters of laying hens transported during hot-dry season. Ninety, 22 weeks old indigenous hybrid Shika Brown layer (SBL) hens were randomly divided into three groups of 30 each, and three replicates of 10 birds within each group. The first group was administered vitamin C at a dosage 200 mg/kg of bodyweight dissolved in 5 ml of sterile water w/v, the second group was administered vitamin E at a dosage 200 mg/kg of bodyweight dissolved in 5 ml edible vegetable oil w/v, while the third group was administered 5ml sterile water (control) v/v only. All administration was through the oral route. All groups were fed basal diet pre- and post experiment. Just before transportation, food and water were withdrawn. Post-transportation, hemoglobin (Hb), packed cell volume (PCV) and blood platelets concentrations were significantly (P < 0.01) and (P < 0.001) reduced in vitamin C treated group; vitamin E and control groups compared with pre-transportation values respectively. However, posttransportation value of red blood cell (RBC) was only significantly (P < 0.05) reduced in control group compared with pre-transportation value. Post-transportation blood chemistry concentrations of total protein (TP) and alkaline phosphatase (ALP) were significantly (P < 0.05) and (P < 0.01) reduced in all experimental groups compared with pre-transportation values respectively. However, posttransportation values of creatine phosphokinase (CPK) and aspartate aminotransferase (AST) were significantly (P < 0.01) and (P < 0.05) reduced in vitamins C and E groups compared with pretransportation values respectively. It is concluded that the administration of antioxidant vitamins C and E alleviated the negative effects of stress in birds transported during the hot-dry season.